Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1530/jrf.0.0790185
|View full text |Cite
|
Sign up to set email alerts
|

Influence of follicular health on the steroidogenic and morphological characteristics of bovine granulosa cells in vitro

Abstract: In 24-h cultures, steroid production by cells from non-atretic follicles increased with increasing follicular diameter. Cells from atretic follicles, of all sizes, produced low amounts of oestradiol-17 beta, but very high amounts of progesterone, relative to cells from non-atretic follicles. Increasing the culture period to 72 h caused little change in daily progesterone and oestradiol-17 beta production by granulosa cells from atretic follicles. In contrast, in cells from non-atretic follicles, daily progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
6
14
0
Order By: Relevance
“…This corresponded also with the results received form the annexin V-FITC test and TUNEL method revealing apoptotic cells. This is in agreement with Henderson et al [61], who found that granulosa cells isolated from non-atretic cow follicles cultured under the influence of testosterone secreted diminishing amounts of progesterone. This confirms that follicles used in our cultures, both granulosal and follicular, were healthy and non-atretic.…”
Section: Discussionsupporting
confidence: 93%
“…This corresponded also with the results received form the annexin V-FITC test and TUNEL method revealing apoptotic cells. This is in agreement with Henderson et al [61], who found that granulosa cells isolated from non-atretic cow follicles cultured under the influence of testosterone secreted diminishing amounts of progesterone. This confirms that follicles used in our cultures, both granulosal and follicular, were healthy and non-atretic.…”
Section: Discussionsupporting
confidence: 93%
“…Atresia was associated with a gradual decrease in follistatin expression by granulosa cells, as during atresia of the ovine follicle (Braw-Tal 1994). Theca interna cells remained morphologically and functionally healthy during the early stages of atresia, expressing all three of the mRNAs studied here, and continued to produce steroids (McNatty et al 1984a, Henderson et al 1987, Jolly et al 1994. As atresia progressed, there was a decrease in all three mRNAs expression in thecal cells, and apoptotic cells were occasionally detected.…”
Section: Discussionmentioning
confidence: 73%
“…These studies also found either a lower level of E 2 (Irving- Rodgers et al 2003b) or no significant reduction (McNatty et al 1984) respectively at these sizes of follicles. In a latter study, however, significant differences in E 2 production by cultured granulosa cells from follicles classified as healthy and atretic were observed (Henderson et al 1987), indicating that there is a difference in granulosa cells in Figure 6 A cartoon of antral (A) and basal (B) atresia illustrating the changes over three time points as cell death progresses either from the apical regions or from the basal region. In basal atresia, the known changes in follicular fluid hormone, expression of steroidogenic enzymes in the apical cells, breaching of the follicular basal lamina and migration of cells from the theca including macrophages, and death of steroidogenic cells and endothelial cells in the theca and changes in insulin-like factor 3 in the thecal interna are indicated.…”
Section: Atresia Of Antral Follicles !5 MM In Diametermentioning
confidence: 78%